Diagnosing REM sleep behavior disorder in Parkinson's disease without a gold standard: a latent-class model study. Issue 7 (4th April 2020) - Figorilli, Michela; Marques, Ana R; Meloni, Mario; Zibetti, Maurizio; Pereira, Bruno; Lambert, Celine; Puligheddu, Monica; Cicolin, Alessandro; Lopiano, Leonardo; Durif, Franck; Fantini, Maria L
Abstract: Study Objectives: To ascertain whether current diagnostic criteria for REM sleep behavior disorder (RBD) are appropriate in patients with Parkinson's disease (PD) consulting a movement disorder center, to evaluate the accuracy of REM sleep without atonia (RSWA) thresholds and determine the value of screening questionnaires to discriminate PD patients with RBD. Methods: One hundred twenty-eight consecutive PD patients (M = 80; mean age: 65.6 ± 8.3 years) underwent screening questionnaires, followed by a sleep-focused interview and a full-night video-polysomnography (vPSG). Without a gold standard, latent class models (LCMs) were applied to create an unobserved ("latent") variable. Sensitivity analysis was performed using RSWA cutoff derived from two visual scoring methods. Finally, we assessed the respective diagnostic performance of each diagnostic criterion for RBD and of the screening questionnaires. Results: According to the best LCM-derived model, patients having either "history" or "video" with RSWA or alternatively showing both "history" and "video" without RSWA were classified as having RBD. Using both SINBAR and Montreal scoring methods, RSWA criterion showed the highest sensitivity while concomitant history of RBD and vPSG-documented behaviors, regardless to presence of RSWA, displayed the highest specificity. Currently recommended diagnostic threshold of RSWA was found to be optimal in our large cohort of PD patients. Both the RBD screening questionnaire (RBDSQ) and the RBD single question (RBD1Q) showed poor sensitivity and specificity. Conclusions: Results of the best LCM for diagnosis of RBD in PD were consistent with the current diagnostic criteria. Moreover, RBD might be considered in those PD patients with both history and vPSG-documented dream enactment behaviors, but with RSWA values within the normal range.